اﻟﻔﺗﺢ اﻹﺳﻼﻣﻲ ﻟﺑﺧﺎرى ﻓﻲ اﻟﻣﺻﺎدر اﻟﻌرﺑﯾﺔ (Journal of the College of Education for Women, 2019)
The Arab Muslime Paid agreat attention to the Islamic East, especially after their conquest to the Parisian lands, they went forword to continue their conquest till Transoxiara (the lands beyond the river). The research is included the Islamic efforts to conquest (Transoxiara) , They needed mouch time for more than 40 years to conquest it. To sattle their steps in it they used its leading figures to prevent the breaking of the agreement held between them as they were known for doing this before more than once. The main idea of this research is releated to study that history in the Arabic resources.